Utilization of Cognitive Diagnostic Assessment (CDA) As A Feedback Tool by Secondary School Teachers in Maiduguri Metropolis, Borno State - Abani, F. , Shettima,; Jidda A., Gabasa; Gazali,, H. B. (Kashere Journal of Education, 2021)
The study determined the utilization of cognitive diagnostic assessment (CDA) as a tool for feedback among secondary school teachers in Maiduguri Metropolis, Borno State. The objectives of the study were to determine level of utilisation of cognitive diagnostic assessment as a tool for feedback among secondary school teachers and if there are statistically significant differences in the level of utilization among teachers of secondary schools due to the variables of academic qualification, years of experience and gender. The study used exploratory survey research design to obtain data for the study. The target population for this study was all secondary school teachers in Maiduguri metropolis, Borno state. There were 3,170 secondary school teachers within the metropolis as at May, 2021. The sample for the study was one hundred and eighty-five teachers randomly sampled. The instrument for data collection was a researcher designed questionnaire consisting of 19 items. The Cronbach’s Alpha reliability of the instrument was .75. The instrument was administered to the teachers in their offices and was collected on the same day. Percentage and frequency count were used to analyze data on the level of utilization of cognitive diagnostic assessment as a feedback tool by teachers while Krustal Wallis Test Chi-Square was used to analyze data on differences in utilization of cognitive diagnostic assessment among teachers by academic qualification and years of experience. Data on gender difference in utilisation of cognitive diagnostic assessment as among teachers was analysed by means of t-test of independent samples. Results on level of utilization of cognitive diagnostic assessment indicate a high level of utilisation among teachers. On difference in utilisation of cognitive diagnostic assessment the study found no significant differences among teachers by academic qualifications and years of experience. The result however indicates a significant gender difference in utilisation of cognitive diagnostic assessment among teachers in favour of females.